(untitled) (Medicine Today, 2012)
Organ dysfunctions are frequent after major burn trauma. Development of MODS in severely burned patients is highly fatal. The present study was conducted to elucidate the etiology and quantify the Multiple Organ Dysfunction (MODS) in major burn patients. Multiple organ dysfunctions in major burnt patients was a prospective analytic study. A total of thirty patients were included in the study, which was conducted in the Burn and Plastic Surgery unit, Bir Hospital, Kathmondu, Nepal over the period of eighteen months from January 2002 to June 2003. Patients with acute major burn i.e. 24 hours from the time of injury were admitted and included in the study. All patients were initially treated in the ICU of burn unit. Among 30 patients, 25 patients were in the age group 15-30 years and 5 patients were in the 31- 60 years age group. 12 patients were male and 18 were female. 93.3% of patients in this study had sustained flame burn and the chief mode of burn injury was accidental 50% whereas 46.7% were suicidal. 66.7% of the patients had 20% - 50%TBSA and 33.3% had sustained 50% - 90% TBSA burn. Majority of the patients were under went early excision and SSG with regular dressing. 63.3 % (19 patients) develop multiple organ dysfunctions and most frequently involved organ was kidneys and followed by lungs, liver and pancreas. Among the multiple organ failure patients, 10 had developed septicemia. None of the patients were found to have developed cardiac failure. The mortality in the study population was 46.7%, all of them had MODS and 9 of them had inhalation injury. It was also seen that MODS can Medicine Today 2010 Volume 22 Number 02 Page 75-79 DOI: http://dx.doi.org/10.3329/medtoday.v22i2.12438